Pengajaran Bilingual di Sekolah Dasar: Kajian Tahapan, Manfaat, dan Tantangannya - Akbar, Zidan Muhammad Rizqi; Miftah, Bangun Zaenal; Labibah, Ravina Kaltsum; Febriani, Mawarna; Khasanah, Isna Yatul; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the implementation of bilingual learning in improving the English language skills of elementary school students. This research is a qualitative research with literature study method. The data sources used come from various literatures, journals, and previous research results that are relevant to the topic of bilingual learning. The data collection technique is done through literature study or literature study which is analyzed descriptively. This study examines several important aspects, namely the definition of bilingual learning, objectives, benefits, stages of implementation, challenges, and implementation strategies in the elementary school environment. The results of this study show that bilingual learning has an important role in improving students’ communication, cognitive and cross-cultural understanding skills. Although faced with challenges such as limited resources and teacher abilities, the application of appropriate strategies can support the effectiveness of the learning process. The conclusion of this study is that bilingual learning can be effectively implemented in elementary schools with good planning and management, so as to improve students’ language competence in facing the era of globalization.